Systems of psychology as epistemology of psychology: technical supplies and conceptual bases for psychology education - Catriel Fierro; Ornella Bruna; Laureano Brisuela Blume; Agostina Vorano (Interacciones)
Resuming the framework outlined in a previous analysis, the present work describes a proposal for teaching systems of psychology based on parameters of meta-theoretical analysis and specific meta-scientific models, with the aim of relocating psychological systems’ courses in systematology of psychology as a component of the epistemology of psychology. Three central issues for systematology in psychologists’ education are described: the importance of working with primary sources through specific pedagogical resources with the aim of developing scientific competences and attitudes, the need to have one (or several) sets of fixed parameters to comparatively analyze theoretical systems, and the problems, criteria and options available when contextualizing such comparative meta-theoretical analysis in comprehensive meta-scientific models which belong to the philosophy of science and of psychology. We conclude on the need to transcend the teaching of systematology as a verbal enunciation of concepts proposed by 'great authors', and on certain risks and limitations regarding the teaching of psychological systems conceived as an epistemological exercise.